High-energy electrical burn of the hand treated with skin grafting: case report. - Carrillo - Barraza , S., (Revista de Ciencias Médicas Torreón, 2026)
An electrical burn is a severe tissue injury that occurs when an electric current flows through the body, turning it into a conductor and generating internal heat. This case report describes a 52-year-old male patient admitted to the emergency department with an electrical burn and an Allman type III left clavicle fracture. A multidisciplinary approach and early rehabilitation are essential to optimize functional outcomes, reduce complications, and preserve hand function, which is a key factor in the patient’s quality of life.